A triplet
(
x
,
y
,
z
)
of positive integers is said to be evil if
x 2 1 3 + y 2 1 9 9 6 = 1 9 9 7 z .
Find the number of evil triplets.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The problem only specifies that x, y, and z must be integers, not necessarily positive. Thus, the triplets with negative x or y should be counted as well. This yields a total of 7 × 2 2 = 2 8 .
Log in to reply
Thanks for pointing this out.
Those who have previously answered 28 have been marked correct. I see that Souryahjit has added "positive" into the question, so the correct answer is 7.
as the only constraint on x,y,z is that they are integers. So,the negative values for x and y should be considered and the ans should be 7*4=28
$frac{13}{x^2}$+$frac{1996}{y^2}$=$frac{z}{1997}$ now cross multiplying you get $x^2y^2z$=$1997(13y^2+1996x^2)$ =$1997(13y^2+499(2x)^2$ now 1997,13,499 all are primes , therefore as x,y,z are integers z=1997 k where k is nothing but $(13y^2+499 4 x^2)/(x^2 y^2)$ now both $x^2$ and $y^2$ are factors of the numerator , therefore notice that there is a factor of x^2 in the numerator , therefore y=kx, now as there is a factor of y^2 as well k can only be 1 or 2 as 4 is present in the term having x^2 , now check for both cases , i.e $y=x$ & $y=2x$ in the original equation you get 7
Eh, you might want to try improving your L a T e X .
Problem Loading...
Note Loading...
Set Loading...
Let x = d x 1 and y = d y 1 where d = g c d ( x , y and g c d ( x 1 , y 1 ) = 1
Hence, d 2 x 1 2 1 3 + d 2 y 1 2 1 9 9 6 = 1 9 9 7 z
or, 1 9 9 7 ( 1 3 ) y 1 2 + 1 9 9 7 ( 1 9 9 6 ) x 1 2 = d 2 z x 1 2 y 1 2
Hence, x 1 2 ∣ 1 9 9 7 × 1 3 and y 1 2 ∣ 1 9 9 7 × 1 9 9 6
Now, note that 1 9 9 7 is square-free and 1 9 9 6 = 2 2 × 4 9 9
Hence, ( x 1 , y 1 ) = ( 1 , 1 ) o r ( 1 , 2 )
Case 1
( x 1 , y 1 ) = ( 1 , 1 )
Therefore, d 2 z = 1 9 9 7 × 1 3 + 1 9 9 7 × 1 9 9 6
or, d 2 z = 1 9 9 7 ( 1 3 + 1 9 9 6 ) = 1 9 9 7 . 7 2
Hence, d = 1 or 7
( x , y , z ) = ( 1 , 1 , 4 0 1 1 9 7 3 ) , ( 7 , 7 , 8 1 8 7 7 )
Case 2
( x 1 , y 1 ) = ( 1 , 2 )
d 2 z = ( 1 3 + 4 9 9 ) 1 9 9 7 = 1 9 9 7 . 2 9
These give ( x , y , z ) = ( 1 , 2 , 1 0 2 2 4 6 9 ) , ( 2 , 4 , 2 5 5 6 1 6 ) , ( 4 , 8 , 6 3 9 0 4 ) , ( 8 , 1 6 , 1 5 9 7 6 ) , ( 1 6 , 3 2 , 3 9 9 4 )